Pengukuran Efisiensi Biaya Menggunakan Analisis Varians (Studi Kasus Pada Proyek Rumah Tinggal CV. Batara Mandiri) - Sahidah; Sarmila (Insan Cita Bongaya Research Journal, 2022)
This study aims to measure the level of cost efficiency by using variance analysis. The research was conducted on CV BATARA MANDIRI with the object of analysis of variance analysis on the Residential Project at Minasa Indah Residence Housing. Data collection techniques use documentation related to cost reports. The analysis technique uses variance analysis, which explains the difference between standard costs and actual costs. The results showed that the implementation of standard costs has an impact on cost efficiency. This can be seen from the results of research on CV. BATARA MANDIRI of the 12 jobs carried out 10 of them have efficient criteria. Jobs that have efficient value include: Preparatory Work, Earthwork, Couple and Plastering Work, Concrete Work, Door Work, Windows and Bowenlis, Roof Work, Ceiling Work, Floorwork, Electrical Work, Sanitair Work, all have a percentage of variance between interval classes -1.33% to 3.30%, While Very Inefficient Work includes Iron Work, Locks, Glass, and Hangers, Cat-catan work, has a percentage of variance between 12.59% to 17.22%.